Evaluation of Skin Irritation Level and Effectiveness of Foot Sleeping Mask Containing Tengkawang Fat in Nanostructured Lipid Carriers System - Fidayanti, Ayu; Mayangsari, Fransisca Dita; Pratiwi, Elasari Dwi (Jurnal FARMASIMED (JFM), 2025)
One of the export commodities from the Non-Timber Forest Products (NTFP) group is tengkawang fruit. This fruit can be processed into fat which has properties similar to cocoa butter. The advantage of this fat compared to cocoa butter is that the price is relatively cheaper. However, the use of tengkawang fat in cosmetics is not widely known. Therefore, researchers are interested in developing cosmetic products based on tengkawang fat to treat xerosis of the feet. To increase occlusivity, tengkawang fat is formulated into an NLC (Nanostructured Lipid Carriers) system. In this research, a foot sleeping mask product was made containing NLC tengkawang fat with the addition of gel (to improve viscosity) and sweet orange oil (to improve aroma). The aim of this research was to determine the irritation skin level and effectiveness of moisturizing the skin of the soles of the feet from a foot sleeping mask containing NLC tengkawang fat. The results of the physical characteristics test show that the foot sleeping mask made meets the desired specifications. The results of skin irritation tests with 35 panelists showed that there was no redness or edema on the panelists' skin during 24, 48 and 72 hours of observation. The results of the moisture effectiveness test showed that the average moisture content of the soles of the panelists' feet on day 0 was 34.531%, while on day 28 (4 weeks) it was 42.815%. There was an increase in humidity of 8.284% during 4 weeks of use. The conclusion of this research is that a foot sleeping mask containing Tengkawang fat NLC can increase the moisture of the skin of the soles of the feet by 8.284% during 4 weeks of use.